INTEGRATED SEDIMENTOLOGY, ICHNOLOGY AND PETROGRAPHY OF THE WEST CROCKER FORMATION (OLIGOCENE TO EARLY MIOCENE), IN NORTH KOTA KINABALU- TUARAN AREA, SABAH, MALAYSIA - MOHAMED, MUHAMAMD AZFAR (2015)
The Oligocene-Early Miocene of West Crocker Formation is well exposed in the Northwest Sabah, Borneo. The integration of sedimentology, ichnology and petrography studies were carried out on seven well-exposed outcrops in this area to characterise the facies, facies associations, ichnology and petrography to interpret the deposition environment of the successions. Eight sedimentary facies have been identified which constitute three main facies groups: (1) sand-dominated facies (Fl, F2, F3, and F4), (2) poorly-sorted unit of mixed sand and mud-dominated facies (F5) and (3) mud-dominated facies (F6, F7, and F8). These are: Fl- graded sandstone (massive to planar laminated), F2-thick amalgamated sandstone, F3-ripple-cross laminated, wavy and convolute lamination sandstone, F4-climbing cross-ripple laminated very fine-grained sandstone, F5-chaotic beds of mixed sandstone and mudstone blocks and clasts, F6-lenticular bedded of sandstone, F7-finely laminated mudstone and siltstone, F8-shale. These facies are group into four facies associations namely FA1- channel-levee, FA2- channelised lobes, FA3- distal lobes, and FA4- chaotic mass complex.